Current/Voltage Dual-Mode Single-Wire Simultaneous Bidirectional Interface Architecture for Sensor System - Kim, Jeong Kyun; Jee, Dong Woo (IEEE Transactions on Biomedical Circuits and Systems, 2020)
This paper presents a simultaneous bidirectional asymmetrical serial interface architecture for sensor systems. The proposed current/voltage dual-mode signaling scheme provides system synchronous clock and continuous data transmission between sensor integrated circuit (IC) and system-on-a-chip (SoC) using a single wire, which minimizes pin requirements on packages. Two types of transceiver circuits were implemented in a 65 nm CMOS technology for the sensor IC and the SoC, and they were designed for transmission rates of 1 Mb/s and 250 Kb/s, core areas of 0.008 mm2 and 0.142 mm2, and power consumptions of 7.1 μW and 145.8 μW, respectively. The transceiver circuit for the sensor IC was also applied to a monolithic PPG sensor implemented in 180 nm CMOS, and the acquisition and transmission of PPG sensor data with the transceiver for the SoC, implemented in 65 nm, was successfully achieved.
Keywords: Bidirectional; Sensor applications; simultaneous; Single-ended; Wearable interfaces; Biosensing Techniques; Electric Wiring; Equipment Design; Lab-On-A-Chip Devices; Wearable Electronic Devices; Bidirectional; I/O interface; sensor application; simultaneous; single-ended signaling; technology scalable; wearable interface